Annual review of health care management revisiting the evolution of health systems organization - Goes, Jim; Savage, Grant T. 1954-; Friedman, Leonard H. (Advances in health care management, 2013)
Dramatic changes to the structure of health systems since the 1980s has seen the development of large, integrated health organizations designed to provide scale and scope advantages, improve the quality of care and health outcomes, and provide greater bargaining power relative to payers and large employers. This transition has led to greater interest in understanding hospitals and health systems as complex systems. Two important themes emerged from this effort: 1. Creation and organization of physician-health organizations, and alignment of these organizations with hospital or system structure; and 2. Viewing health care organizations as complex systems, leading to new perspectives on design and management of these organizations. In Volume 15, Reuben McDaniel and L. Robert Burns, authors of two influential articles on these themes from earlier volumes of AHCM, revisit the evolution of health systems organization in light of regulatory and organizational evolution in health care, including the Patient Protection and Accountable Care Act of 2010, and increasing consolidation of health systems. Five additional refereed papers assess the latest evidence on physician integration, complexity, and system redesign.